The Effectiveness of Health Education through Animation Videos on Mothers' Knowledge of Breast Milk Management - Yuni Kristiani Tumani; NiLuh Ayu Anggraeny; Nazwa Noverlita; Ni Luh Febi Dian Sari; Ofni Imanuela (Poltekkes Kemenkes Palu, 2025)
Background: The percentage of breastfeeding to babies directly breastfeeding to mothers has decreased, for reasons that breast milk does not come out, separate from mothers, and other medical reasons. This results in the mother's breasts feeling full, so the mother is uncomfortable. To avoid giving formula milk to the baby, mothers can express and store breast milk. Therefore, health education related to the management of breast milk is very important to be given to mothers to provide knowledge and awareness to mothers to be able to provide exclusive breastfeeding to their babies. Methods: This study used a pretest-posttest one group design on 60 breastfeeding mothers who had babies aged 0-6 months in August 2025. In the study, health education was provided through an animated video about the management of breast milk. The analysis used frequency distribution, Paired Sample T-Test statistical test and effectiveness test. Results: The average increase in mothers' knowledge about the management of breast milk with a difference of 3.55. The correlation value was 0.555 (>r table 0.254), p-value was 0.000 (<0.05), the effectiveness value of the animated video was 67.62% and was included in the effective category (>66.6%). Conclusion: Influential animated videos are significantly and effectively used as a health education.